Balancing the high tech and high touch in education: the implementation of humanistic approach on edu-recreation concept in politeknik pariwisata bali - Ida Bagus Putu Puja; Putu Ayu Aryasih; Desak Gede Chandra Widayanthi (Institut Pariwisata dan Bisnis Internasional, 2021)
The implementation of a humanistic approach in educational institutions could be guidance in balancing High Tech and High Touch. The humanistic approach is defined as a physical and spiritual activity to maximize the development process, as well as an effort to master the treasures of knowledge in a series of overall personality formations. This research is qualitative research that analyzes the application of the humanistic approach in the design of the Edu-Recreation concept at the Bali Tourism Polytechnic (Politeknik Pariwisata Bali) through the study of documents and other literature, and also observation and interview. The results of the research are proposed as input for developing existing designs so that they can have a more significant influence in improving the quality of education at the Bali Tourism Polytechnic. As the result, the Edu-Recreation concept design at the Bali Tourism Polytechnic has implemented values in the humanistic education approach, namely the development of the affective aspects of students and the freedom to develop self-potential.